The Global Financial Crisis and Workers' Remittances to Africa : What's the Damage? - Chami, Ralph; Barajas, Adolfo; Fullenkamp, Connel; Garg, Anjali (Washington, D.C. : International Monetary Fund, 2010)
Using data on the distribution of migrants from Africa, GDP growth forecasts for host countries, and after estimating remittance multipliers in recipient countries, this paper estimates the impact of the global economic crisis on African GDP via the remittance channel during 2009-2010. It forecasts remittance declines into African countries of between 3 and 14 percentage points, with migrants to Europe hardest hit while migrants within Africa relatively unaffected by the crisis. The estimated impact on GDP for relatively remittance-dependent countries is 2 percent for 2009, but will likely be short-lived, as host country income is projected to rise in 2010.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet